2012
DOI: 10.1111/j.1442-2042.2012.03135.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical hyaluronic acid for interstitial cystitis/painful bladder syndrome: A comparative randomized assessment of different regimens

Abstract: Abbreviations & AcronymsObjectives: To compare the clinical effectiveness of different regimens of intravesical hyaluronic acid instillation for patients with interstitial cystitis/painful bladder syndrome. Methods: A total of 60 patients (age 16-77 years) diagnosed with interstitial cystitis/ painful bladder syndrome were enrolled in this prospective, randomized study. A total of 30 patients were assigned to receive four weekly intravesical instillations of 40 mg of hyaluronic acid followed by five monthly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
0
31
1
Order By: Relevance
“…The final systematic review and meta-analysis included 10 eligible articles and 8 subsets with HA and 4 subsets with HA/CS. However, analyzed studies numbered 12 in the current metaanalysis because Gulpinar et al [18] reported the results of Hyacyst ® (120 mg HA in 50 ml) and Ialuril ® (1.6% HA and 2.0% CS), and Lai et al [20] reported the separate results of HA instillation for IC/PBS with 2 different regimens: 4 weekly intravesical instillations of 40 mg HA followed by 5 monthly HA instillations (HA-9 group), and 12 intravesical instillations of 40 mg HA every 2 weeks (HA-12 group). Therefore, we counted these as 4 studies in the data extraction process (Table 1) after searching the articles (Fig.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…The final systematic review and meta-analysis included 10 eligible articles and 8 subsets with HA and 4 subsets with HA/CS. However, analyzed studies numbered 12 in the current metaanalysis because Gulpinar et al [18] reported the results of Hyacyst ® (120 mg HA in 50 ml) and Ialuril ® (1.6% HA and 2.0% CS), and Lai et al [20] reported the separate results of HA instillation for IC/PBS with 2 different regimens: 4 weekly intravesical instillations of 40 mg HA followed by 5 monthly HA instillations (HA-9 group), and 12 intravesical instillations of 40 mg HA every 2 weeks (HA-12 group). Therefore, we counted these as 4 studies in the data extraction process (Table 1) after searching the articles (Fig.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 90%
“…Lai et al compared the clinical effectiveness of two different intravesical HA instillation regimen (HA-9: 4 weekly intravesical instillations of 40 mg HA followed by 5 monthly HA instillations HA-12: 12 intravesical instillations of 40 mg HA every 2 weeks) [20]. However, most studies adopted a treatment strategy consisting of weekly treatment for several weeks followed by maintenance treatment (Table 1).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…140,141 Intravesicular replenishment of GAG as a treatment for IC/PBS has yielded mixed results. [142][143][144][145][146] Additionally, the clinical relevance of urothelial permeability in IC/PBS remains controversial. [147][148] Finally, the role of mast cells in IC/PBS has been investigated for several decades.…”
Section: Interstitial Cystitis/painful Bladder Syndromementioning
confidence: 99%
“…The final set of 19 articles on intravesical BPS/IC therapy was further qualitatively and quantitatively analysed: 5 studies were prospective controlled trials [34][35][36][37][38], 1 compared different intravesical products [39], 1 paper was designed as a retrospective study [40], and another 1 compared two different regimens of the same product [41]. The rest of the trials were classified as uncontrolled clinical studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Other relevant differences were also detected: six of the studies included Btreatment-refractory patients^, considered to be cases with an inadequate response to previous BPS/IC treatments such as intravesical DMSO [15], heparin and/or PPS [15,41] and/or oral drug therapy [24,43,47]. One study only included Bnaïve patients^(no previous disease-specific treatment) with a positive PST and a reduction of≥2 points in symptom score after the first instillation of ChS 0.2 % [44].…”
Section: Patients Characteristicsmentioning
confidence: 99%